Investigation of Student Performance in an Interrelated Service Delivery Approach - Carolyn Cooper; Barbara Thopmson; Greg Gaither (Journal of Research in Rural Education, 1983)
The purpose of this study was to compare academic progress and behavioral ratings of students receiving special education services in interrelated (multicategorical) classrooms to those of students enrolled in the more traditional categorical service delivery system. Subjects were 92 mildly handicapped students (40 learning disabled, 34 mildly retarded, and 18 emotionally disturbed) who attended school in two rural special education cooperatives. Equally divided between the two special education programs, the subjects were matched on exceptionality and age. Measures of academic performance on selected subtests of the Woodcock-Johnson Psycho-Educational Battery and behavior ratings from the Behavior Rating Profile were obtained through pre- and post-testing conducted during October and May. Although most students made substantial gains, no significant differences were found between students served in categorical and interrelated classroom settings.